Institutionalisation of rape: an analysis of its spaces of normalisation - Santos-de-Torregroza, Lorena (Las Torres de Lucca. International Journal of Political Philosophy, 2025)
This article aims to broaden the understanding of rape by analysing different spaces such as war, prison, university campuses, churches, marriage, and the family, where rape is institutionalised as an integral part of their functioning, fulfilling a function or serving a cause, and where the institutionalisation of rape is not as evident at first glance as it is in prostitution or the pornography industry. The concept of spaces of rape does not refer to institutional spaces where rape happens to occur but to a structural reality of these spaces of social life where rape is embedded and normalised in socially accepted practices and justified by the belief systems that define them.